1995
DOI: 10.1080/10934529509376252
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics of DNAPLs in sand packs: Water‐influx displacement

Abstract: Flow behavior studies were conducted to determine if complex organic wastes can be adequately modeled using representative compounds. The complex organic waste used was a sample from the Petro-Processors Superfund Site. The model compound was 1,1,2-trichloroethane (TCA). Waterfloods were performed in uniformly packed sand columns using different flow scenarios. Recovery efficiencies and flow characteristics of the waste sample and TCA were compared. Samples of recovered waste were analyzed for priority polluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Little, if any, work has been conducted on the impact that such additives have on the IFTs of CHSs. On the other hand, changes in the wettability of quartz surfaces arising from the adsorption of compounds from the NAPL phase have been examined by a number of researchers (13)(14)(15). Powers and Tamblin (13) and Harrold et al (14) have demonstrated that the adsorption of amines can reduce the water wetting preference of quartz surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Little, if any, work has been conducted on the impact that such additives have on the IFTs of CHSs. On the other hand, changes in the wettability of quartz surfaces arising from the adsorption of compounds from the NAPL phase have been examined by a number of researchers (13)(14)(15). Powers and Tamblin (13) and Harrold et al (14) have demonstrated that the adsorption of amines can reduce the water wetting preference of quartz surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Powers and Tamblin (13) and Harrold et al (14) have demonstrated that the adsorption of amines can reduce the water wetting preference of quartz surfaces. Similarly Thakur et al (15) undertook a series of water-flood experiments using lab 1,1,2-trichloroethane and a complex DNAPL mixture recovered from the Petro-Processors Superfund site. The differences in flow characteristics between the two DNAPLs were attributed, in part, to mineral wettability changes (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies, in which recovery efficiencies were studied under laboratory conditions using both laboratory and field materials, efficiencies between the two materials were quite different. Thakur et al (1995) investigated the use of a laboratory grade DNAPL as a substitute for a field DNAPL in determining the effectiveness of a waterflooding scenario. The authors noted that although the experimental set-up was the same for each run, the recovery of the field DNAPL exhibited significantly more variation than the laboratory results.…”
Section: Remediation Of Field Non-aqueous Phase Liquidsmentioning
confidence: 99%
“…These experiments indicate that not only does the presence of the dye decrease the IFT of the PCE in water and ethanol, it can also increase the density and viscosity of the remedial solutions, which can decrease the effectiveness of the remediation. When any chemical is added to a DNAPL to be used in experiments, including the use of dyes for visualization, it should be documented and the potential alterations to the IFT of the mixture and wettability of the porous medium should be determined.There have not been many studies on the effects of remediation techniques on field DNAPLs under laboratory conditions Thakur et al (1995). investigated the effects of using a field versus laboratory grade DNAPL on the effectiveness of waterflooding as a remediation technique.…”
mentioning
confidence: 99%